Real-world outcomes of immunotherapy with or without chemotherapy in first-line treatment of advanced non-small cell lung cancer - Pelicon, Veronika; Cufer, Tanja; Knez, Lea (Frontiers in Oncology, 2023)
Background Immunotherapy alone (mono-IT) or combined with chemotherapy (chemo-IT) has recently become the cornerstone of first-line treatment for advanced non-small cell lung cancer (NSCLC) patients. Here, real-world outcomes of first-line mono-IT and chemo-IT of advanced NSCLC treated within routine clinical practice at a single academic center in the Central Eastern European (CEE) region are presented. Materials and methods A total of 176 consecutive patients with advanced NSCLC treated with mono-IT (118 patients) or chemo-IT (58 patients) were included. At the participating institution, all medical data relevant for providing oncology care are collected prospectively and in a standardized manner using purposely created pro-forms. Adverse events (AEs) were recorded and graded according to Common Terminology Criteria for Adverse Events (CTCAE). The Kaplan−Meier method was used to estimate median overall survival (mOS) and median duration of treatment (mDOT). Results The 118 patients in the mono-IT cohort had a median age of 64 years, most were male (59%), 20% had ECOG PS ≥2, and 14% had controlled CNS metastases at baseline. With a median follow-up time (mFU) of 24.1 months, the mOS was 19.4 months (95% CI, 11.1-27.6), and the mDOT was 5.0 months (95% CI, 3.5-6.5). The 1-year OS was 62%. The 58 patients in the chemo-IT cohort had a median age of 64 years, most were male (64%), 9% had ECOG PS ≥2, and 7% had controlled CNS metastases at baseline. With a mFU of 15.5 months, the mOS was 21.3 months (95% CI, 15.9-26.7), and the mDOT was 12.0 months (95% CI, 8.3-15.6). The 1-year OS was 75%. Adverse events of severe grade were recorded in 18% and 26% of patients, and immunotherapy discontinuation due to AEs occurred in 19% and 9% in the mono-IT and chemo-IT groups, respectively. No treatment-related deaths were recorded. Conclusion The results from the present real-world observational study from a CEE country suggest similar effectiveness and safety of first-line mono-IT and chemo-IT in patients with advanced NSCLC to those observed in randomized clinical trials. However, continuous follow-up will offer better insight into the magnitude of long-term benefits in routine clinical practice.